FAKTOR-FAKTOR YANG MEMENGARUHI KEPATUHAN WAJIB PAJAK DENGAN PEREDARAN BRUTO TERTENTU MELALUI PENDEKATAN PERILAKU - Yoda Mustikasasti, Elvanes; Usman, Fadlil (Politeknik Keuangan Negara STAN, 2019)
This research is a survey conducted on taxpayers with specific gross circulation in the area of KPP Pratama Pondok Aren. The title of this research is